Case study of application of capillary active thermal insulation systems used as an interior insulation for historical buildings (2019)
The trend of reducing energy consumption and the impact of human activities on nature, has increased significantly in recent years. This trend is also noticeable in civil engineering industry. It has an impact not only on new, but also on restored or adapted buildings. Buildings such as monuments or historical buildings are also included in this category. It’s necessary to realize that in case of these types of buildings, there are other values which are more important than technical parameters which should be considered. Mainly it is the social, artistic and craftsmanship value of these buildings. In connection with these types of buildings, the application of interior thermal insulation is usually suggested method to improve thermal parameters of walls and reduce energy consumption. Application of these systems appears to be the most appropriate way to preserve values mentioned above. Modern material research also takes place in this area and brings new developed materials such as capillary active isolation systems. Capillary active insulations solve some of the problems connected with the addition of a thermal insulation on the inner side mentioned in [14]. This paper brings hygro-thermal analysis of four types of mentioned systems applied on massive one-layer masonry made of fireclay bricks, what is most common wall type of historical buildings in Slovakia. These types are thermal insulation plaster, multi-layer system predominantly made of wood-fiber and active layer, calcium silicate system and system made of polyurethane boards with grid of holes filled with capillary active material.